The Best Phone Store, Intelligent Recommendation System for Smartphone Selection - Asmawati, Endah; Limanto, Susana; Heru Arwoko; Mario Matthew Cardinal Vincent (Keluwih: Jurnal Sains dan Teknologi, 2026)
Abstract— Nowadays, smartphones are a primary item that is needed by almost everyone, from children to adults. The large number of smartphones on the market makes it difficult for consumers to find a smartphone that suits their needs. Each person usually has many considerations (criteria) in choosing the best smartphone for themselves. Each smartphone offers something interesting with different advantages. This often makes prospective buyers confused to choose the right smartphone according to their needs. Many applications have been developed to help prospective smartphone buyers overcome the difficulty of choosing a smartphone, but the smartphone recommendation applications that are developed usually use alternatives stored in a static database, making them less suitable for use in the future, where new smartphones continue to emerge. In addition, the circulating applications do not provide default weight values ​​for the selection criteria. This condition can cause confusion among prospective buyers who have limited smartphone knowledge. "The Best Phone Store" was created to help prospective smartphone buyers choose smartphones according to their preferences. Prospective buyers can input the weight of the criteria according to their wishes, but if they do not input it, the system will calculate based on the default weight that already exists. Recommendations are made using the Simple Additive Weighting method. Based on the results of external trials to prospective smartphone buyers, more than 80% of respondents stated that the application can provide detailed information about smartphones, the criteria given are in accordance with the preferences of prospective buyers, recommendations make it easier for them to choose a smartphone according to the desired criteria. Keywords: recommendation, simple additive weighting, smartphone Abstrak—Saat ini smartphone merupakan barang primer yang diperlukan hampir semua orang, mulai anak-anak sampai orang tua. Banyaknya smartphone yang beredar di pasaran membuat orang kebingunan untuk mencari smartphone yang cocok dengan kepentingannya. Setiap orang biasanya mempunyai banyak pertimbangan (kriteria) dalam memilih smartphone yang terbaik untuk dirinya.Setiap smartphone menawarkan hal yang menarik dengan kelebihan yang berbeda-beda. Hal ini yang seringkali membuat calon pemeli kebingungan untuk memilih smartphone yang tepat sesuai dengan kebutuhannya. Banyak aplikasi telah dikembangkan untuk membantu calon pembeli smartphonr mengatasi kesulitam dalam memilih smartphone, namun aplikasi rekomendasi smartphone yang dikembangkan biasanya menggunakan alternatif yang disimpan dalam database statis sehingga kurang cocok untuk digunakan di masa depan, di mana smartphone baru terus bermunculan. Selain itu, aplikasi yang beredar tidak memberikan nilai bobot default untuk kriteria seleksi. Kondisi ini dapat menimbulkan kebingungan di kalangan calon pembeli yang memiliki pengetahuan smartphone yang terbatas. ”The Best Phone Store” diciptakan untuk membantu calon pembeli smartphone dalam memilih smartphone sesuai dengan preferensinya. Calon pembeli dapat menginputkan bobot kriteria sesuai dengan keinginnya, namun jika tidak menginputkan maka sistem akan menghitung berdasarkan default bobot yang sudah ada. Rekomendasi ditentukan dengan menggunakan metode Simple Additive Weighting. Berdasarkan hasil ujicoba eksternal kepada calon pembeli smartphone, lebih dari 80% responden menyatakan aplikasi bisa memberikan informasi rinci tentang smartphone, kriteria yang diberikan sesuai dengan preferensi calon pembeli, rekomendasi memudahkan mereka dalam memilih smartphone sesuai dengan kriteria yang diinginkan. Kata kunci: recommendation, Simple Additive Weighting, smarthphone